ANALISIS EFEKTIVITAS ORGANIZATIONAL CITIZENSHIP BEHAVIOR (STUDI KASUS KEPOLISIAN NEGARA REPUBLIK INDONESIA DI POLRES MEMPAWAH) - Yeremia Niaga Atlantika; Blasius Manggu; Sabinus Beni; Yosua Damas Sadewo (Balitbangda Provinsi Lampung, 2022)
Organizational Citizenship Behavior (OCB) is an individual's discretionary behavior, not directly related to or explicitly recognized by the reward system and that in aggregate promotes the effective functioning of the organization, OCB continues to expand into multiple disciplines such as human resources, marketing, health administration, hospital, economy, community psychology, and military psychology. This research was based on a case study within the Mempawah Police Resort, involving 9 informants consisting of key informants and triangulation informants as primary data. The purpose of this research was to know the effective’s OBC within the Mempawah Police Resort in supporting the duties, protecting, and serving the people of Mempawah Regency. The kind of this research was descriptive, and the data had been analyzed qualitatively using NVivo 12 plus. The results show that OCB had an effective role in building effective and dynamic communication, building a sense of sincerity and sincerity, increasing discipline, building a sense of responsibility, and building high commitment from members of Mempawah Police Station.